2016
DOI: 10.20524/aog.2016.0037
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in patients with liver cirrhosis

Abstract: There is ongoing evidence that vitamin D is related to the pathophysiology of cirrhosis. Although the incidence of vitamin D deficiency in chronic liver diseases and cirrhosis is strongly documented, its pathogenic association with advanced liver fibrosis remains controversial. There is evidence of a significant relation of 25(OH)D levels with the degree of liver dysfunction, considering that an inverse correlation of 25(OH)D levels with both Child-Pugh score and Model for End-Stage Liver Disease has been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 83 publications
2
57
1
6
Order By: Relevance
“…Hormonal differences between genders may partially explain the higher incidence of frailty in females compared to males . Some of these hormonal changes are mirrored in cirrhosis …”
Section: Pathophysiologymentioning
confidence: 99%
“…Hormonal differences between genders may partially explain the higher incidence of frailty in females compared to males . Some of these hormonal changes are mirrored in cirrhosis …”
Section: Pathophysiologymentioning
confidence: 99%
“…23 Low vitamin D serum concentration significantly correlates with liver diseases, including nonalcoholic fatty liver disease 24 and hepatitis B. 25,26 Vitamin D deficiency leads to higher levels of HBV replication, which increases the risk of infection and often leads to poor outcomes in patients with liver cirrhosis. 25,26 Moreover, temperature and light have also been shown to play a role in regulating DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Vitamin D deficiency leads to higher levels of HBV replication, which increases the risk of infection and often leads to poor outcomes in patients with liver cirrhosis. 25,26 Moreover, temperature and light have also been shown to play a role in regulating DNA methylation. 27 Fitting for our study, it is also shown that aberrant GSTP1 promoter methylation is associated with the development of ACLF and its prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials and meta-analyses have strongly linked vitamin D deficiency with liver fibrosis progression, regardless the aetiology of chronic liver disease, with unclear causality relationship whether liver morbidity, affects vitamin D synthesis or the vitamin deficiency and is the contributor in the development of liver pathology. [15] The current study tested the hypothesis of vitamin D deficiency and HBV replication in 96 HBeAg negative non-cirrhotic chronic HBV patients; in this study, the nullification of many factors that could negatively implicate the harmony of the results was maximally done, like inclusion of patients without significant fibrosis, HBeAg negative, matched age and sex, vitamin D sample withdrawal in the same month, and so on.…”
Section: Discussionmentioning
confidence: 99%